2015
DOI: 10.1007/s12186-015-9131-6
|View full text |Cite
|
Sign up to set email alerts
|

Great Expectations: The Relationship Between Future Time Perspective, Learning from Others, and Employability

Abstract: Employees in countries with advanced industrial economies need to continuously develop their competences to sustain their employability -that is, to have a set of competences that enables them to maintain or find an adequate job. But how should efforts to enhance employability progress in the context of the demographic shift? Previous research suggests that employees' perspective about their future working life may influence their motivation to engage in learning activities. The study reported and discussed he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 78 publications
1
34
0
1
Order By: Relevance
“…The challenge for employers lies in the utilization of the potential of employees of various categories. Employers who want to utilize the potential of their staff in a longer time period must come up with new models of work that will be attractive for both parties (Joniaková and Blšťáková, 2015;Froehlich, Beausaert, Segers, 2015). Kulik, Ryan, Harper, George (2014) add that organisations must implement new creative methods to be able to attract, motivate and maintain an ageing workforce.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge for employers lies in the utilization of the potential of employees of various categories. Employers who want to utilize the potential of their staff in a longer time period must come up with new models of work that will be attractive for both parties (Joniaková and Blšťáková, 2015;Froehlich, Beausaert, Segers, 2015). Kulik, Ryan, Harper, George (2014) add that organisations must implement new creative methods to be able to attract, motivate and maintain an ageing workforce.…”
Section: Discussionmentioning
confidence: 99%
“…As confirmed by many studies (Galea et al, 2014;Askenazy, 2013;Mohrenweiser and Zwick, 2009), the agricultural sector is no exception in this regard. Although the use of flexible working time organisation is also influenced by the type of a job, a wide range of flexible working time organisations makes it possible to use them in agriculture, especially for different age groups (Principi and Fabbietti, 2015;Ciutiene and Railaite, 2015;Froehlich et al, 2015;Urbancová and Hudáková, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The transition process as a whole is built upon informal learning or social learning activities in the work environment, which comprise of talking and collaborating with colleagues, consulting each other on a regular basis, learning trough feedback, sharing resources, observing, imitating, and/or mentoring others (Kwakman 2003;Lohman 2006). It has been demonstrated that this kind of informal learning leads to improved performance (Froehilich et al 2015). In innovation processes the social learning process is further strengthened by shared mutual goals, reframing, and commitment (Rijst et al 2018).…”
Section: University Professionalization On the Job: An Engineering Edmentioning
confidence: 99%